Landscape, Place, Space and the Mind in the Old English Psalms: A Study Centred on the Paris Psalter (Bibliothèque nationale de France, fonds latin MS 8824) - Pascoe-Van Zyl, Elizabeth Ann (Trinity College Dublin. School of English. Discipline of English, 2026)
Despite much excellent scholarship on landscape, place and space, the mind and emotion, and the psalms in early medieval England, an extended study of how these phenomena may be interrelated is yet to emerge. Given the ubiquity of the psalms in the period, it stands to reason that these texts may have had an indelible effect on perceptions of the remaining aspects, listed above, especially considering the following: people entering a monastic house (and sometimes lay nobility), in early medieval England, could be required to memorize and internalize all 150 psalms in order to become psalteratus or psalterata and psalm texts, themselves, not only express a range of powerful emotions, they are also replete with landscape (trees, mountains, water features and so forth) place (locus amoenus and locus horribilis) and space (pathway) imagery. This thesis addresses this current gap in the literature. It does so by analysing the intersection of landscape, place and space imagery and the mind in the singular, bilingual (the 150 Romanum Latin psalms appear alongside the first fifty Old English Prose Psalms and the remaining one hundred Old English Metrical Psalms), parallel-text iteration of the psalms in early medieval England – the Paris Psalter. I argue for the need to direct close attention to how psalmic images, in both Latin and the vernacular, shaped the thought life and, in turn, influenced both perceptions of the surrounding environment as well as the creative output of persons (the psalterati/ae) who had memorized and internalized these texts. The first three chapters focus on the bilingual psalm texts and physical manuscript. The final chapter harnesses the fact that the Metrical Psalms are both Old English psalms as well as the longest piece of continuous vernacular poetry in the corpus to move outside the Paris Psalter and trace the tacit influence of psalmic diction (within the three categories) in some Old English poetry. Major findings include the following themes. The overarching valence of the tree image in Psalm 1 – the entire psalter’s ‘gateway’ – potentially shaped not only the iconography in the manuscript but also the tree/cross image complex in The Dream of the Rood poem. In both the Prose and Metrical Psalms, the respective paraphrast and psalm-poet display a fine lexical sensitivity in their selection of landscape terms, for example mountains and water features, which they occasionally insert without a Latin exemplar. Read against the toponymic evidence, these choices suggest how a differentiated awareness of the surrounding environment influenced an engagement with the psalms’ landscape imagery – as seen, especially, in the paraphrast’s singular use of cnoll ‘knoll’ and the psalm-poet’s discriminating deployment of burna ‘stream’. This praxis moves toward a landscape-inflected psalmic hermeneutic that is potentially more widely applicable when viewed alongside the manuscript’s illustration programme which emphasises the landscape with repeated use of ‘groundlines’. The psalter’s root metaphors of ‘pathway’ and ‘refuge’ along with ‘water-path’ psalmic diction (such as semitas maris ‘paths of the sea’ in Psalm 8. 9) are all tacitly evinced in poems such as The Wanderer and The Seafarer. And psalmic pathways could also, perhaps, be behind the unusually long and narrow dimensions (and design) of the manuscript itself. In sum, then, this study has investigated, drawing on the Paris Psalter, how the psalms in both Latin and the vernacular shaped early medieval English perceptions of landscape, place and space. It proposes that psalmic imagery influenced both conceptions of the broader environment and artistic/literary production among the psalterati/ae.
APPROVED
Keywords: Latin (Roman) Psalms; Old English Prose Psalms; Old English Metrical Psalms; The Paris Psalter Manuscript; Landscape; Place; Space